2010
DOI: 10.1149/1.3484498
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Electrolytes and Reference Electrodes for Alkaline Polymer Electrolyte Membrane Fuel Cells

Abstract: This article presents an introduction to the state-of-the-art understanding and recent developments [publicly available] of alkaline polymer electrolyte membrane fuel cells. The major issues with the characterization of alkaline anion-exchange membranes (including radiation-grafted types) and the development of a practical in situ reference electrode system will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…2. This effect has been shown previously in other materials 12,29,30 and is attributed to rapid conversion of hydroxide to a mixed hydroxide/bicarbonate/carbonate form upon exposure to atmospheric CO 2 .…”
Section: Hydroxide Ion Conductivitysupporting
confidence: 77%
“…2. This effect has been shown previously in other materials 12,29,30 and is attributed to rapid conversion of hydroxide to a mixed hydroxide/bicarbonate/carbonate form upon exposure to atmospheric CO 2 .…”
Section: Hydroxide Ion Conductivitysupporting
confidence: 77%
“…The peroxidated ETFE films then act as a solid-state free-radical initiator for the subsequent graft polymerization step. After irradiation, the films were transported back to the laboratory in dry ice before they were stored in a freezer at À40 C (the peroxide groups are stable for around 6 months at this temperature [27]). …”
Section: Tj Omasta Et Al / Journal Of Power Sources XXX (2017) 1e9mentioning
confidence: 99%
“…It is widely understood that these reactions occur quickly . It can be problematic to accurately calculate their intrinsic rate because, in relevant systems, the transformation may be limited by CO 2 mass transport.…”
Section: Effect Of Co2 On Oh− In Aemsmentioning
confidence: 99%
“…found that half of the initial amount of OH − anions was replaced in the first 10 min of exposure of the AEM to ambient air, but complete replacement of all OH − anions took 6 h . This was consistent with the work of Kizewski et al., which showed that OH − was fully replaced after 1 h, and after 4 h the AEM was in a mixed HCO 3 − /CO 3 2− form. All reported data on ex situ AEM carbonation is summarized in Table .…”
Section: Effect Of Co2 On Oh− In Aemsmentioning
confidence: 99%